(untitled) (Discourse of Law and Administration, 2022)
Pursuant to the amendment of July 4, 2019 to the Code of Civil Procedure the legislator allowed the examination of certain social insurance cases in simplified proceedings. Therefore, unless the court makes use of the possibility of omitting the provisions on simplified proceedings when examining these cases, lodging a cassation complaint in these cases will be inadmissible pursuant to Article 3982 § 2 point 3 of the Code of Civil Procedure. The subject of this article is an assessment of the effects of this solution, which has been shown to be incorrect for at least three reasons. Firstly, it is contrary to the basic objective of a cassation complaint, i.e. the implementation of the public interest expressed in the unification of jurisprudence. Secondly, this solution is also inconsistent with the purpose of distinguishing proceedings in social insurance cases, expressed in the protection of the person lodging an appeal to a civil court. Thirdly, it violates the constitutional principle of equality, because the admissibility of lodging a cassation complaint in the same category of cases depends on the court’s decision to hear or not hear the case in accordance with the provisions on simplified proceedings. As a result, a postulate to allow the lodging of a cassation complaint in all social insurance cases in accordance with the general principles contained in Article 3982 § 1 of the Code of Civil Procedure was expressed irrespective of whether such a case has been heard or not in the simplified proceedings.